RARE-26. WHOLE GENOME SEQUENCING OF AN OSSEOUS METASTASIS DURING CHECKPOINT-CONTROLLED INTRACRANIAL GLIOBLASTOMA REVEALS NEW INSIGHTS INTO POTENTIAL MECHANISMS OF IMMUNE ESCAPE - Mohme, Malte (Neuro Oncol, 2019)
Glioblastoma (GBM) has a devastating prognosis and recent advances in the treatment of a variety of cancer entities, e.g. through checkpoint inhibition, could so far not be translated into improved outcome in newly-diagnosed GBM. Characterizing rare cases of peripheral metastases which succeeded in overcoming immune control, can help to understand the mechanisms of immune escape. Here we describe the first reported case of a detailed genetic and immunological characterization of a peripheral bone metastasis from a GBM which was controlled intracranially by anti-PD1 checkpoint inhibition We performed whole genome sequencing (WGS) of the primary- and recurrent tumor, as well as the bone metastasis. Genomic data was analyzed for copy number variations and mutational profiles. In addition, immune monitoring with flow cytometric phenotyping and next-generation sequencing of the peripheral T-cell repertoire was used. A 70-year old patient developed multiple osseous metastases in the spine, while his IDHwt GBM recurrence was immunologically controlled with checkpoint inhibition. Biopsy confirmed peripheral GBM metastases. Immunophenotyping reflected the effective activation of the peripheral T-cell response, with, however, simultaneous upregulation of regulatory T-cells during disease progression. WGS sequencing demonstrated a distinct molecular profile of the GBM metastasis, with amplifications in chromosome 3 and 9, as well as genomic loss on chromosomes 4, 10 and 11. The peripheral metastasis was distinguished by mutations in mismatch repair genes, such as MSH4 and MLH1, associated with a hypermutated phenotype. Among the mutated genes we found potential candidates involved in immune escape of circulating tumor cells. This case represents a unique opportunity to analyze potential mechanisms of GBM-mediated immune escape during immune activation with anti-PD1 checkpoint therapy. It highlights the fact, that although an effective, disinhibited immune response can control the cranial GBM disease, hypermutated tumor clones can evade the tumor-specific T-cell response and disseminate to distant organs.